2022
DOI: 10.1186/s13613-022-00990-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor lysis syndrome, acute kidney injury and disease-free survival in critically ill patients requiring urgent chemotherapy

Abstract: Background Tumor lysis syndrome (TLS) is a life-threatening complication during the treatment of malignant neoplasia. We sought to describe characteristics and predictors of acute kidney injury (AKI), remission and mortality in high-risk TLS patients. In this retrospective monocentric study, we included all patients with the diagnosis of biological and/or clinical TLS from 2012 to 2018. The primary outcome was the prevalence of AKI during the acute phase of TLS. Secondary outcomes were overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…Additionally, in accordance with previous studies, TLS following CAR-T therapy showed detrimental effects on patient prognosis, clinical response, PFS and OS. Acute kidney injury (AKI) had high prevalence during the acute phase of TLS and was reported as a major cause of death in TLS with an OR of 10.41 for in-hospital mortality ( 17 19 ). In our cohort, TLS related AKI resulted in ICU administration, renal replacement therapy and 30-day modality.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in accordance with previous studies, TLS following CAR-T therapy showed detrimental effects on patient prognosis, clinical response, PFS and OS. Acute kidney injury (AKI) had high prevalence during the acute phase of TLS and was reported as a major cause of death in TLS with an OR of 10.41 for in-hospital mortality ( 17 19 ). In our cohort, TLS related AKI resulted in ICU administration, renal replacement therapy and 30-day modality.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumors were mostly large bulky masses (with a median largest transverse dimension of about 9 cm), commonly located in the lungs, colon, or liver [ 2 , 6 , 20 , 46 , 93 ]. Most patients had been diagnosed with metastatic disease mainly in the liver and/or lungs and had an unfavorable prognosis compared to previous studies on STLS of hematological malignancies [ 94 ]. There was a significantly higher likelihood of STLS-specific death in patients with metastatic disease – especially in those with liver or lungs involvement – compared to those without diagnosis of metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…[ 73 ] TLS may sometimes resemble sepsis and present with acute respiratory failure, hemodynamic instability, and systemic inflammatory response syndrome. Abdel-Nabey et al [ 78 ] reported that in 153 TLS patients admitted into intensive care, AKI was reported in 82% of the patients.…”
Section: Cancer Complications Cause Renal Injurymentioning
confidence: 99%
“…It was reported that delayed hyperuricemia treatment might have long-term effects. [ 78 ] Identifying high-risk TLS patients as soon as possible to prevent TLS and TLS-induced AKI is crucial. [ 80 ] The cornerstone of TLS care is hydration and hypouricemic medications (allopurinol and rasburicase).…”
Section: Cancer Complications Cause Renal Injurymentioning
confidence: 99%